"Arc‐continent collision" of the Aleutian‐Komandorsky arc into Kamchatka: Insight into Quaternary tectonic segmentation through Pleistocene marine terraces and morphometric analysis of fluvial drainage. Issue 4 (20th July 2013) - Pedoja, K.; Authemayou, C.; Pinegina, T.; Bourgeois, J.; Nexer, M.; Delcaillau, B.; Regard, V.
<x xml:space="preserve">Abstract</x> [1] At the NW corner of the Pacific region, just south of the Kamchatsky Peninsula, the northern tip of the Pacific plate subduction and associated volcanic arc interacts with the western end of the Aleutian‐Komandorsky dextral transform plate boundary and associated arc. Study of both Holocene and Pleistocene sequences of uplifted marine terraces and also of fluvial drainage patterns on the Kamchatsky Peninsula allows us to highlight active tectonics produced by complex plate interaction. Our results show that the central eastern coast of the peninsula is currently divided into four different zones consisting in uplifted blocks associated with various uplift rates in front of a fold‐and‐thrust zone to the west. Our main tectonic benchmark—the altitude of the shoreline correlated to the Last Interglacial Maximum (Marine Isotopic Stage 5e)—yields late Pleistocene uplift rates ranging from 0.2 to 2.74 mm/yr. One of the main active faults bounding the coastal blocks is dextral and is interpreted as a prolongation of an offshore fault of the Aleutian‐Komandorsky dextral transform plate boundary. We suggest that structures on the Kamchatsky Peninsula accommodate a part of the transform motion, but that mainly, the arc‐continent collision of the Aleutian arc against Kamchatka produces a "bulldozer" effect on the Kamchatsky Peninsula.